Examining the Impact of Cognitive Strategies on Health Outcomes in Vietnamese Healthcare - Kuiếnc, Tùongh; Văn, Le Thanh; Minh, Nam; Son, Bao (Journal of Asian-african Focus in Health, 2024)
This study explores the role of cognitive strategies in enhancing health outcomes within the Vietnamese healthcare system, addressing a gap in the literature regarding their application in Southeast Asia. A total of 300 participants, including healthcare professionals and patients, were surveyed to assess the use and effectiveness of cognitive strategies such as attention focusing, memory aids, problem-solving approaches, and behavioral reinforcement. The results revealed that attention focusing was the most frequently used strategy (63.3%), followed by memory aids (56.7%), and problem-solving (43.3%). The study found significant positive correlations between cognitive strategies and key health outcomes, including treatment compliance (r = 0.45), lifestyle choices (healthy diet, r = 0.50), and preventive health behaviors (exercise, r = 0.38). Urban participants were more likely to use cognitive strategies compared to their rural counterparts, highlighting the urban-rural divide in healthcare access and strategy implementation. Multiple regression analysis indicated that attention focusing and memory aids significantly predicted treatment compliance, while problem-solving and behavioral reinforcement influenced healthy diet choices and exercise habits. These findings underscore the potential of cognitive strategies to improve health outcomes in Vietnam, emphasizing the need for context-specific interventions that account for cultural and regional differences. The study contributes to the global understanding of cognitive strategies in healthcare, particularly in non-Western contexts, and offers insights for healthcare practitioners and policymakers seeking to implement evidence-based, patient-centered approaches in Vietnam and similar settings.